ANALISIS FUNGSI MANAJEMEN POAC DALAM ADMINISTRASI PENDIDIKAN PAUD: STUDI KASUS KEBUTUHAN DIGITALISASI DI KB INDAH PERMAI - Citra Ayu; Dhea Yunika; Meta Rosalia; Mida Destiani; Rosalina Destyaningsi; Syaza Aulia Alpinia; Dwi Noviani (MANAJERIAL : Jurnal Inovasi Manajemen dan Supervisi Pendidikan, 2026)
ABSTRACT Effective educational administration is an important factor in supporting the quality of early childhood education services. However, administrative management at KB Indah Permai, Tanjung Agung Village, still faces challenges because most processes are conducted manually and supported by a limited number of educators. This study aimed to analyze the effectiveness of educational administration based on the POAC (Planning, Organizing, Actuating, Controlling) management functions and to identify the need for administrative digitalization. The study employed a descriptive qualitative approach. Data were collected through observation, interviews, and documentation in February 2026, involving the principal and teachers as research informants. Data were analyzed through data reduction, data display, and conclusion drawing. The results showed that the implementation of POAC functions had been carried out fairly well through program planning, task distribution, learning implementation, and administrative supervision. However, administrative effectiveness had not been fully optimized because activity documentation, data management, and child development evaluations were still limited, while teachers experienced relatively high workloads. The novelty of this study lies in mapping the digitalization needs of early childhood education administration based on the POAC framework. Therefore, administrative digitalization is needed to improve data management efficiency, support decision-making processes, reduce educators’ administrative workload, and strengthen the quality of governance and early childhood education services in a sustainable manner. ABSTRAK Administrasi pendidikan yang efektif merupakan faktor penting dalam mendukung kualitas layanan PAUD. Namun, pengelolaan administrasi di KB Indah Permai Desa Tanjung Agung masih menghadapi kendala karena sebagian besar proses dilakukan secara manual dan didukung oleh jumlah tenaga pendidik yang terbatas. Penelitian ini bertujuan menganalisis efektivitas administrasi pendidikan berdasarkan fungsi manajemen POAC (Planning, Organizing, Actuating, Controlling) serta mengidentifikasi kebutuhan digitalisasi administrasi. Penelitian menggunakan pendekatan kualitatif deskriptif. Data dikumpulkan melalui observasi, wawancara, dan dokumentasi pada Februari 2026 dengan informan kepala sekolah dan guru. Analisis data dilakukan melalui reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa penerapan fungsi POAC telah berjalan cukup baik melalui perencanaan program, pembagian tugas, pelaksanaan pembelajaran, dan pengawasan administrasi. Namun, efektivitas administrasi belum optimal karena dokumentasi kegiatan, pengelolaan data, dan evaluasi perkembangan anak masih dilakukan secara terbatas, sementara beban kerja guru relatif tinggi. Kebaruan penelitian ini terletak pada pemetaan kebutuhan digitalisasi administrasi PAUD berdasarkan fungsi POAC. Dengan demikian, digitalisasi administrasi diperlukan untuk meningkatkan efisiensi pengelolaan data, mendukung pengambilan keputusan, mengurangi beban administratif pendidik, serta memperkuat kualitas tata kelola dan layanan PAUD secara berkelanjutan.